Impactos da mudança do uso e cobertura do solo na emissão de óxido nitroso e abundância de bactérias desnitrificantes no solo - Nishisaka, Caroline Sayuri (Universidade Federal de São Carlos, 2018)
Agriculture is responsible for 80% of nitrous oxide emissions on earth's atmosphere, the most potential greenhouse gas among the three main gases (CO2, CH4 and N2O). Citriculture and silviculture play an important role on Brazilian economics due to the high demand of orange and wood products for exportation. Thus, in order to get a better understand about the role of those cultures on N2O emission, this research aims to evaluate N2O emissions from Citrus sinensis and Eucalyptus spp. crops, adjacent forests of each agriculture field were used as control. Citrus and eucalyptus sites are located in Sorocaba and Salto de Pirapora municipality, both in the state of Sao Paulo, Brazil. In each agriculture field and adjacent forest, eight static chambers were randomly installed, and gas sample were collected during dry and wet region season. Soil samples were collected in each field of study from five random sampling points, for further physicochemical, molecular analysis and microcosm incubation. Gas samples were collected from microcosm after moisture adjustment in 70% of field capacity. All gas samples were analyzed by gas chromatography technique. The number of copies of genes related to denitrifying process (nirK, nirS e nosZ) was determined by quantitative real time PCR. Seasonality had significant (P<0.05) influence on N2O emission in field, and N2O fluxes in incubated soil. It was observed positive correlation among dissolved organic carbon (DOC) concentration on soil, soil and plant residue total carbon and nitrogen content and N2O emissions. High nirK, nirS and nosZ gene abundance was found on soil collected during wet season, comparing to those collected on dry season, in both field and microcosm, which was correlated with DOC content and soil moisture. However, there were not significant differences on genes abundance comparisons between cultivated soils and adjacent forests. In conclusion, the seasonality has influence in both N2O emission and denitrifying bacteria abundance present in citrus- and eucalyptus-cultivated soils, mainly through the effects on soil and plant residue physicochemical characteristics, especially those related to COD and soil moisture.
Impacts of land change use and plant residue on nitrous oxide emission and denitrifying bacteria abundance on soil
Keywords: Desnitrificação; Gases do efeito estufa; Microbiota do solo; Eucalipto; Citrus; Denitrification; Greenhouse gas; Soil microbiome; Eucalyptus; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO